"Placing oneself on the other side": how teachers' dispositions toward research can be constructed through pedagogical documentation. A case study in Spain. Issue 2 (15th March 2023) - Maldonado-Ruiz, Gonzalo; Soto Gómez, Encarnación
ABSTRACT: The following paper presents the results of a case study on the educational potentiality of pedagogical documentation as a way to construct the research disposition of preschool teachers in initial education. After an introductory reflection on the relevance of provoking the reconstruction of practical knowledge, pedagogical documentation is approached as it is proposed in Reggio Emilia preschools (Italy). This contribution presents as its fundamental findings the potentiality of pedagogical documentation as a way to enter into a dialogue with the complexity of teacher education processes. It is argued that this tool can be essential to weave research into a preschool teacher's day-to-day action. Although participating students are initially uncomfortable using the tool, finally they end up mobilising each of the five constituent dimensions of teachers' practical knowledge (attitudes, values, emotions, skills and knowledge).